Rituximab for induction and maintenance therapy of granulomatosis with polyangiitis: a single-centre cohort study on 114 patients. (2nd May 2018) - Puéchal, Xavier; Iudici, Michele; Calich, Ana Luisa; Vivot, Alexandre; Terrier, Benjamin; Régent, Alexis; Cohen, Pascal; Jeunne, Claire Le; Mouthon, Luc; Ravaud, Philippe; Guillevin, Loïc
Abstract: Objectives: To assess efficacy and safety of rituximab (RTX) induction and maintenance therapy for granulomatosis with polyangiitis (GPA) in a single-centre cohort study. Methods: All patients with active GPA, not enrolled in trials, who received ⩾1 RTX infusion(s) for induction were included. At remission, protocolized maintenance RTX infusions were given every 6 months for 18 months. Kaplan–Meier curves were used to estimate survival rates. Univariable analyses identified factors associated with remission failure and relapse, and Cox models retained independent predictors of relapse. Results: One hundred and fourteen adults with relapsing (65%), refractory/grumbling (22%) or new-onset (13%) GPA received RTX for induction; 100 were given ⩾1 RTX maintenance infusion(s) and 90 received 500 mg every 6 months. Median daily prednisone induction dose was 30 mg; 76% of patients were still receiving a median daily prednisone dose of 5 mg at 2 years. Median follow-up was 3.6 years. Respective 2-year relapse-free survival and RTX retention rates were 85 and 78%. Serious infection and serious adverse event rates were 4.9 and 8.1 per 100 patient-years, respectively. Refractory/grumbling vs new-onset and/or relapsing GPA ( P < 0.01 for each individually; P < 0.001 vs the latter two taken together), pachymeningitis ( P < 0.05), pure granulomatous disease ( P < 0.05) or estimated glomerular filtration rate ⩾60 ml/min ( P < 0.01) were associated with remission failure. Multivariate analyses retained refractory/grumbling GPA ( P = 0.05), subglottic stenosis ( P < 0.005), ENT involvement ( P = 0.01) and skin involvement ( P < 0.0005) as independent predictors of relapse. Conclusion: RTX induction and low-dose preemptive maintenance can effectively and safely induce sustained remission in GPA in a real-life setting.